Analisis Respons Pengurus PPGT Terhadap Pemuda Pindah Agama Menggunakan Teori Paul F. Knitter - Helda Tulak (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: The purpose of this study was to find out the response of PPGT management to young people who changed religions at the Kalembang Congregation, Sangalla' Barat Class using Paul F. Knitter's theory. In completing this paper, the authors use qualitative research methods. Where the author collects data through observation and interviews with 8 PPGT administrators as informants. Data obtained from observation and interviews, data reduction was carried out. Then the data from the reduction results are presented and then analyzed using Paul F. Knitter's theory. Through this research it was found that of the 8 PPGT administrators who became informants, 5 of them namely RP, MT, M, YLA and NST were included in the acceptance model. MP is a follower of the fulfillment model. YS is a follower of the replacement model. Meanwhile, MSD is a follower of the mutuality model. At the end of this paper, the authors hope that there will be things done by various parties to address this issue. Keywords: Changing Religion, Response of PPGT Management, Paul F. Knitter. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui respons pengurus PPGT terhadap pemuda pindah agama di Jemaat Kalembang, Klasis Sangalla’ Barat menggunakan teori Paul F. Knitter. Dalam merampungkan tulisan ini, penulis menggunakan metode penelitian kualitatif. Di mana penulis mengumpulkan data melalui observasi dan wawancara kepada 8 orang Pengurus PPGT selaku informan. Data yang didapatkan dari observasi dan wawancara, dilakukan reduksi data. Kemudian data dari hasil reduksi disajikan kemudian dianalisis menggunakan teori Paul F. Knitter. Melalui penelitian ini ditemukan bahwa dari 8 orang Pengurus PPGT yang menjadi informan, 5 di antaranya yakni RP, MT, M, YLA dan NST termasuk model penerimaan. MP termasuk penganut model pemenuhan. YS termasuk penganut model penggantian. Sedangkan, MSD termasuk penganut model mutualitas. Di akhir tulisan ini, penulis mengharapkan ada hal yang dilakukan oleh berbagai pihak untuk menyikapi persoalan ini. Kata Kunci: Pindah Agama, Respons Pengurus PPGT, Paul F. Knitter.